Potential application of biodegradable TS/SCFC green composite for disposable packaging food container - Jeefferie , Abdul Razak (2010)
The noble aim of this research is to investigate extensively the potential application of Tapioca Starch (TS) filled Sugar Cane Fiber Cellulose (SCFC) biocomposites for disposable packaging food container. This research was started by preparing and characterizing the SCFC through various characterization tools. The effect of the optimum SCFC loading to the fabricated TS composites was studied as to establish the best formulation of the TS/SCFC biocomposites. The thin sheet of composite samples were then fabricated with different blend formulation via compression molding machine and the samples were cut into the specific dimension, according to the ASTM standard for each different testing. Further testing for various engineering properties of TS/SCFC biocomposites were carried out, such as tensile test, impact test, flexural test and hardness test. These tests were used to determine the mechanical properties of the fabricated composites. Then, it was followed by conducting the physical test such as weathering test, water absorption test and the thickness swelling test. Other than that, the Fourier Transform Infrared (FTIR) analysis was conducted as to investigate the degradation behavior of the biocomposites. In order to observe the fracture morphology of the samples, the optical microscope was utilized comprehensively. Generally, the results of this study have shown good performance for both the mechanical and physical properties of the fabricated composites. However, through the morphological observation on the mechanical and physical testing fractured surfaces, it was clearly found that the adhesion between the SCFC and TS matrix were not well attached. This study has indicated the role of fiber loading into the resulted properties of the fabricated composites. Development of this alternative container material for food packaging application will provide a great potential solution to the environmental friendly and safe packaging medium either for food, consumer or environment as a whole.